Day of a lion [videorecording (DVD)] - Foscht, Bianca; Foscht, Bianca; Foscht, Dilara; Foscht, Dilara; Neviani, Simone (Gravitas Ventures, 2025)
Set in the late 1950s after their father's death, two sisters reunite at their childhood home to uncover forgotten secrets and rip open old wounds. They're soon drawn into a game of cat and mouse in the house of a dead man.